Brexit’s Effect on Arbitration: the Aspects of Anti-Suit Injunction and Investment Arbitration - Okinčic, Sebastjan (Teisė, 2024)
Concentrating on a few material aspects in relation to the broader theme, the article analyses the effect of Brexit on international commercial arbitration. In particular, the piece firstly treats on the most recent UK Case Law in relation to anti-suit injunction – a phenomenon attributable to the Common Law in the context of the earlier European Union courts’ jurisprudence of the said instrument. Secondly, Brexit’s interplay with the ongoing global investment arbitration reform is considered. The article considers the globally recognised UN 1958 New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, on which Brexit had no adverse effect. When analysing the interplay between Brexit and the ongoing global investment arbitration reform, a particular regard is paid to the lack of investment arbitration provisions in the UK-EU Trade and Cooperation Agreement, as well as the termination of various relevant bilateral investment treaties. The article concludes that the influence of arbitration shall continue to grow, anti-suit injunction shall continue to be applied by the United Kingdom courts, and the Brexit’s interplay with the global investment protection overall and the investment arbitration in a particular reform is somewhat consistent.